2012
DOI: 10.1182/blood-2011-06-364976
|View full text |Cite
|
Sign up to set email alerts
|

IRF-8 extinguishes neutrophil production and promotes dendritic cell lineage commitment in both myeloid and lymphoid mouse progenitors

Abstract: IntroductionHSC differentiation occurs through a series of intermediate stages, or progenitors, whereby self-renewal capacity is progressively lost and genetic programs limit the development of alternate cell lineages until commitment to a single cell type is reached. The ability to identify distinct progenitor populations via differential surface marker expression has allowed lineage potentials to be determined, and a hierarchical map of lineage restriction to be inferred. The classic model of hematopoietic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
129
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(140 citation statements)
references
References 50 publications
11
129
0
Order By: Relevance
“…Whether all Irf8 À / À MDPs pass through cMoPs to produce neutrophils is unknown; some Irf8 À / À MDPs may directly differentiate into neutrophils. Interestingly, Bhattacharya and colleagues 17 have recently reported that all lymphoid progenitors (ALPs) from Irf8 À / À mice can produce neutrophils. Therefore Irf8 À / À ALPs may also contribute to neutrophilia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether all Irf8 À / À MDPs pass through cMoPs to produce neutrophils is unknown; some Irf8 À / À MDPs may directly differentiate into neutrophils. Interestingly, Bhattacharya and colleagues 17 have recently reported that all lymphoid progenitors (ALPs) from Irf8 À / À mice can produce neutrophils. Therefore Irf8 À / À ALPs may also contribute to neutrophilia.…”
Section: Discussionmentioning
confidence: 99%
“…IRF8 is required for the generation of mouse monocytes (particularly Ly6C þ monocytes) 9,10 , classical DCs (cDCs; particularly CD8a þ DCs) and plasmacytoid DCs (pDCs) [11][12][13] that express high levels of IRF8 (refs 14,15). At the progenitor level, Irf8 À / À mice harbour increased numbers of GMPs and MDPs but lack common DC progenitors (CDPs) 16,17 . Recent studies have suggested that Irf8 transcript expression is relatively high in MDPs, CDPs and common monocyte progenitors (cMoPs) [18][19][20] .…”
mentioning
confidence: 99%
“…At the progenitor level, Irf8 −/− mice accumulate MDPs but lack CDPs, CD115 − CDPs, and pre-cDCs [11,19,40]. Thus, differentiation arrest occurs between MDPs and CDPs.…”
Section: Regulation Of DC Development By Irf8mentioning
confidence: 99%
“…We infer that the production of neutrophils from MDPs and cMoPs is a major cause of neutrophilia in Irf8 −/− mice, because these progenitors are the first populations at which IRF8 is highly expressed in the myeloid lineage. It should be mentioned that all lymphoid progenitors (ALPs) from Irf8 −/− mice can also produce neutrophils [40], and the differentiation potential of Irf8…”
Section: Regulation Of Neutrophil Development By Irf8mentioning
confidence: 99%
“…[2][3][4] The differentiation and function of cDCs and pDCs is associated with specific transcriptional programs that show some overlap, such as their dependency on interferon regulatory factor 8 (IRF8), 5,6 but are mainly controlled by lineage-specific elements.…”
Section: Classes Of Dcsmentioning
confidence: 99%